2003
DOI: 10.1248/bpb.26.818
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Potential of Fluvastatin <i>via</i> the Inhibition of Nicotinamide Adenine Dinucleotide Phosphate (NADPH) Oxidase Activity

Abstract: Oxidative stress plays a critical role in the pathogenesis of atherosclerosis.1-3) Elevated oxidative stress and superoxide anion generation could promote the conversion of low density lipoprotein (LDL) to atherogenic oxidized LDL (ox-LDL), contributing to atherosclerosis. There is increasing evidence that the oxidative modification of LDL contributes to the formation of foam cells in the artery wall. 4) Concerning the modification of LDL, neutrophils rapidly take up ox-LDL and generate superoxide anions, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…21 The antioxidant action of statins is derived not only from the reduction of oxidized low-density lipoprotein, but from inhibition of NADPH oxidase, which generates superoxide anion (·O2 -) in the vascular wall. 22 FV has a potent antioxidant property as a free radical scavenger, because of its unique chemical structure, 17 but in the present study, however, FV did not reduce the myocardial content of 8-OHdG, which is produced by hydroxylation at the C-8 position of deoxyguanosine by ·OH and is currently used as a stable biomarker of oxidative DNA damage. 18,23 Formation of 8-OHdG in the heart with IR progressively increases after reperfusion and is completely blocked by co-treatment with a free radical scavenger.…”
Section: Antioxidant Property Of Fvcontrasting
confidence: 70%
“…21 The antioxidant action of statins is derived not only from the reduction of oxidized low-density lipoprotein, but from inhibition of NADPH oxidase, which generates superoxide anion (·O2 -) in the vascular wall. 22 FV has a potent antioxidant property as a free radical scavenger, because of its unique chemical structure, 17 but in the present study, however, FV did not reduce the myocardial content of 8-OHdG, which is produced by hydroxylation at the C-8 position of deoxyguanosine by ·OH and is currently used as a stable biomarker of oxidative DNA damage. 18,23 Formation of 8-OHdG in the heart with IR progressively increases after reperfusion and is completely blocked by co-treatment with a free radical scavenger.…”
Section: Antioxidant Property Of Fvcontrasting
confidence: 70%
“…In those studies, 14,15 LPS-induced hyporeactivity to ACh and to different vasoconstrictors could be reversed by intra-arterial infusion of high doses of the antioxidant vitamin C. Despite the lack of a direct antioxidative effect, statins may inhibit key proteins involved in generation of reactive oxygen species. Experimental studies revealed that statins inhibit production of superoxide via the NADPH oxidase system in monocytes, 26 neutrophils, 27 and endothelial cells, 28 because activation of NADPH oxidase is dependent on an isoprenoid group, ie, geranyl geraniol, which derives from HMG-CoA and is thus inhibited by statins. 29 In parallel to these in vitro observations, De Caterina and coworkers 30 found a significant reduction of F2-isoprostane, a product of the attack of reactive oxygen species on esterified arachidonic acid, in patients with hypercholesterolemia who were receiving simvastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism by which pravastatin improved endothelial function is by reducing the oxidative inactivation of NO. Recent investigations have demonstrated that statins can decrease lipid peroxidation production [7] , suppress NADPH oxidase activity [28] , and increase the activity of catalase [29] , and superoxide dismutase [7] , which decreases the generation of oxygen free radicals resulting in reduction of NO activation. Moreover, a number of studies have shown that pravastatin can also reduce superoxide anion production by suppressing PKC activity in vascular cells [14,15] .…”
Section: Discussionmentioning
confidence: 99%